2013
DOI: 10.1111/febs.12447
|View full text |Cite
|
Sign up to set email alerts
|

ModulatoryATPbinding to the E2 state of maize plasma membrane H+ATPase indicated by the kinetics of vanadate inhibition

Abstract: P-type ATPases, as major consumers of cellular ATP in eukaryotic cells, are characterized by the formation of a phosphorylated enzyme intermediate (E2P), a process that is allosterically coupled to translocation of cations against an electrochemical gradient. The catalytic cycle comprises binding of Mg-ATP at the nucleotide-binding domain, phosphorylation of the E1 state (E1), conformational transition to the E2P state, and dephosphorylation through the actuator domain and re-establishment of the E1 state. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…H + transport analysis of membrane vesicles isolated from S. indica showed that preincubation with vanadate (a reversible inhibitor of these specific proton pumps - Wang et al, 2013) reduced the F max by 70%, thus confirming significant plasma membrane ATPase (P-H + -ATPase) activity in this fungus (Figure 3). This reduction in F max was independent of the C availability (2 and 20 g L −1 of glucose) under which the fungus had been grown (Figure 3C).…”
Section: Physiologymentioning
confidence: 73%
See 1 more Smart Citation
“…H + transport analysis of membrane vesicles isolated from S. indica showed that preincubation with vanadate (a reversible inhibitor of these specific proton pumps - Wang et al, 2013) reduced the F max by 70%, thus confirming significant plasma membrane ATPase (P-H + -ATPase) activity in this fungus (Figure 3). This reduction in F max was independent of the C availability (2 and 20 g L −1 of glucose) under which the fungus had been grown (Figure 3C).…”
Section: Physiologymentioning
confidence: 73%
“…The addition of 20 mM NH 4 Cl was used to show a recovery of the fluorescence that indicated a collapse of the preliminarily formed H + gradient. The P-H + -ATPase proton pumping activity was measured with and without vanadate (0.2 mM Na 3 VO 4 , a reversible inhibitor – Wang et al, 2013 ) and the orthovanadate-sensitive activity was attributed to the P-H + -ATPase. Maximum fluorescence (F max ) reflects the steady-state amplitude of the ΔH formation and it was calculated as ΔF/F and expressed as percentage.…”
Section: Methodsmentioning
confidence: 99%
“…GL transport through tonoplast vesicles was dependent on MgATP and effectively inhibited by vanadate. Vanadate is a membrane ATPase inhibitor and represses the function of ABC transporters [30][31][32]. In contrast, neither niflumic acid nor probenecid affected GL transport by tonoplast vesicles.…”
Section: Discussionmentioning
confidence: 98%